Crescimento super e subcrítico de trincas em vidros e vitrocerâmicos analisado via indentacão - Rodrigues, Bruno Poletto (2012)
In this dissertation we quantified properties that may better describe the mechanical behaviour of different glasses and glass-ceramics of the Na2O-CaO-SiO2-P2O5 system, based on the Biosilicate®chemical composition developed by LaMaV-UFSCar, after implantation in the human body. We tried to analyse variables such as n (the stress-corrosion susceptibility coefficient, derived from subcritical crack growth experiments), K0 (KI0, KSCC or Kth, the threshold stress intensity factor below which no subcritical crack growth occ-curs), and to characterize the R-Curve (the increase in fracture toughness as the cracks increase in length). The experimental methods utilized are beased on the materials response to Vickers indentation, whether by following the crack length, statistically analyzing the number of nucleated cracks or breaking indented samples on four point bending testing. These techniques pose the great advantage of being very economic in respect of time needed to prepare the samples and in respect of the number of samples used. The experimental results were, whenever possible, compared with literature data and their validity broadly discussed. From the experimental data its possible to conclude that the tested methods do not generate valid and coherent results concerning the materials and conditions tested, contributing to the con side of a discussion very present on the literature.